GASTROINTESTINAL PARASITES OF SCHOOL CHILDREN IN BENIN CITY, NIGERIA - CE Okaka; AO Awharitoma; JN Okonji (Tehran University of Medical Sciences, 2000)
Examination of faecal samples of 6,430 school children aged between 2 and 20 years, for gastrointestinal parasites using sedimentation and Kato smear techniques was carried out in Benin City, Nigeria between January 1997 and December 1998. Four thousand two hundred and thirty six (65.8%) were infected. Three species of protozoa and 8 species of helminths were recorded as follows: Entamoeba histolytica (6%), Entomoeba coli (4.8%), Giardia lamblia (5.2%), Schistosoma mansoni (2.4%), Fasciola gigantica (2.3%), Taenia sp. (1.3%), Ascaris lumbricoides (17.0%), Enterobius vemicularis (1.5%), Trichuris trichiura (6.8%), Necator americanus (13.9%), and Strongyloides stercoralis (3.9%). Prevalence of infection increased with increase in age to a maximum value of 8.15% among the 6-9 years age group (junior primary pupils) and thereafter decreased with increase in age, to the least value of 28.6% among the 17-20 years old (senior secondary). The nursery pupils recorded the highest prevalence for protozoa and the nematode Ascaris lumbricoides infections while the senior primary pupils had the highest infection rates for the fluke Schistosoma mansoni and for all other nematode parasites recorded (apart from Ascaris). The junior secondary pupils recorded the highest prevalence for the liver fluke, Fasicola gigantica while the senior secondary pupils recorded the least prevalence for all the parasitic infections. Infections were significantly high (P<0.05) in the rainy season (April-October) and low in the dry season (November-March). The high infection rate is considered to be due to general poor sanitation in the environment and the poor sanitary habits of children.